2014
DOI: 10.1038/ejcn.2014.45
|View full text |Cite
|
Sign up to set email alerts
|

Revised D-A-CH intake recommendations for folate: how much is needed?

Abstract: The D-A-CH reference value (D-A-CH arises from the initial letters of the common country identification for the countries Germany (D), Austria (A) and Switzerland (CH)) for folate equivalents had been set at 400 μg/d for adults in the year 2000. By that time, the prevention of cardiovascular diseases through reduction of homocysteine was considered an important target of the reference value. Since that time a number of research papers revealed that in spite of an inverse association between folate-rich diet an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 33 publications
0
35
0
3
Order By: Relevance
“…Though the average dietary folate intake (≈200 μg d –1 )7 might be sufficient to prevent severe deficiency in the majority of women from this population, it is not sufficient to prevent NTDs.…”
Section: Introductionmentioning
confidence: 96%
“…Though the average dietary folate intake (≈200 μg d –1 )7 might be sufficient to prevent severe deficiency in the majority of women from this population, it is not sufficient to prevent NTDs.…”
Section: Introductionmentioning
confidence: 96%
“…The recommended dietary allowance (RDA) for folate in German population is 300 μg DFE/day [4] (Table 1), whereas the Institute of Medicine (IOM) of the US National Academy of Sciences set the RDA for folate to 400 μg DFE [5]. Different intake data from the national survey on German population (NVSII 2012) showed a mean folate intake of 200 μg DFE/day [6].…”
Section: Introductionmentioning
confidence: 99%
“…The median intake of dietary folate in young women (19-35 years) is from 170 to 181 μg DFE/day, thus clearly showing that the majority of them are at risk for insufficient intake of folate [6]. To recommend doubling the folate intake from dietary sources [4] (increase by ∼200 μg DFE/day) in the population appears unrealistic. In fact, the German nutrition survey NVSII showed that healthy lifestyle patterns did not predict a difference in dietary folate intake of more than 30 μg DFE/ day [6].…”
Section: Introductionmentioning
confidence: 99%
“…Данные рекомендации согласуются с мнением других европейских и американ-ских специалистов. Совместный анализ результатов дота-ции фолиевой кислоты, проведенный немецкими, швей-царскими и австрийскими специалистами, подтвердил, что минимально эффективной дозой является суточная доза 400 мкг [44]. Верхний порог дозы фолиевой кислоты с целью профилактики не должен достигать 1000 мкг/сут.…”
unclassified
“…До получения дополнительных сведений, применение левомефолата в РОССИЙСКИЙ ВЕСТНИК АКУШЕРА-ГИНЕКОЛОГА 1,2015 составе витаминных комплексов и контрацептивов более обосновано у женщин с подтвержденной недостаточно-стью МТГФР. В настоящее время европейские эксперты рекомендуют на этапе прегравидарной подготовки и во время беременности прием синтетической фолиевой кис-лоты [44], а FDA напоминает, что левомефолат кальция и фолиевая кислота не являются эквивалентными веще-ствами, и обязывает производителей указывать, какой именно фолат содержит биодобавка или лекарственный препарат. В Европе было проведено рандомизированное, двойное слепое плацебо-контролируемое клиническое исследование, в котором сравнили влияние применения метилфолата ([6S]-5-метилтетра гидро фолата) и фолиевой кислоты на концентрацию фолатов в плазме и эритроци-тах в течение 24 недель у женщин детородного возраста (18-49 лет).…”
unclassified